Queer in STEM: Workplace Experiences Reported in a National Survey of LGBTQA Individuals in Science, Technology, Engineering, and Mathematics Careers. Issue 1 (2nd January 2016) - Yoder, Jeremy B.; Mattheis, Allison
ABSTRACT: A survey of individuals working in science, technology, engineering, and mathematics (STEM) fields who identify as lesbian, gay, bisexual, trans*, queer, or asexual (LGTBQA) was administered online in 2013. Participants completed a 58-item questionnaire to report their professional areas of expertise, levels of education, geographic location, and gender and sexual identities and rated their work and social communities as welcoming or hostile to queer identities. An analysis of 1, 427 responses to this survey provided the first broad portrait of this population, and it revealed trends related to workplace practices that can inform efforts to improve queer inclusivity in STEM workplaces.